Low carbon technologies for agriculture: a study on rice and wheat production systems in the Indo-Gangetic plains - Pathak, Himanshu; Aggarwal, Pramod K. (Indian Agricultural Research Institute, 2012)
Global warming is a prominent environmental issue of the twenty-first century. Agriculture contributes to the global warming primarily through the emission and consumption of greenhouse gases (GHGs), viz. methane, nitrous oxide and carbon dioxide. The major sources of emission of GHGs in the agriculture sector are enteric fermentation, rice cultivation, agricultural soils, manure management and on-field burning of crop residue. There are some indirect sources also like manufacturing of fertilizers, pesticides, herbicides, etc. Therefore, it is highly pertinent to develop such technologies that help in reducing GHGs emission from agriculture. It will not only mitigate climate change but also reduce consumption of costly inputs by enhancing their use-efficiency causing an increase in farmers income.